Antitumor activity of some prenylated xanthones - Castanheiro, RAP (2009)
Pyranoxanthones 6-8 were obtained by dehydrogenation of the respective dihydropyranoxanthones 3-5 with DDQ in dry dioxane. Two prenylated xanthones 10,11 were obtained from the reaction of 1-hydroxyxanthone (9) with prenyl bromide in alkaline medium, or by condensation of xanthone 9 with isoprene in the presence of orthophosphoric acid. The structural elucidation of the two new compounds 6,11, as well as an update of data for the already described prenylated derivatives 7,8,10 were accomplished by IR, UV, HRMS and NMR ( 1H, 13C, HSQC and HMBC) techniques. The effect of the prenylated xanthone derivatives on the in vitro growth of human tumor cell lines MCF-7 (breast adenocarcinoma) and NCI-H460 (non-small cell lung cancer) is also reported. Compounds 10 and 11 have been found to exhibit a moderate growth inhibitory activity against the MCF-7 cell line. (c) 2009 by the authors; licensee Molecular Diversity Preservation International, Basel, Switzerland.